Circulating homocysteine and folate concentrations and risk of type 2 diabetes: A retrospective observational study in Chinese adults and a Mendelian randomization analysis - Cheng, Yating; Wang, Chen; Zhang, Xiaokang; Zhao, Yue; Jin, Bingyu; Wang, Chunfang; Lu, Zhibing; Zheng, Fang (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: The relation between circulating homocysteine (hcy) and folate concentrations and risk of type 2 diabetes mellitus (T2DM) has been evaluated in several observational studies with inconsistent results; and it is unclear about their causal relationships. Our aim was to assess the causality association between circulating hcy or folate concentrations and the development of T2DM using Mendelian randomization (MR) analysis, based on results of an observational study in Chinese adults. Methods: We conducted an observational study of 370 patients with T2DM and 402 controls after routine physical examination who consulted at the Zhongnan Hospital of Wuhan University between March 2021 and December 2021. Correlations between hcy and folate and the incidence of T2DM were quantified using logistic regression models. Two-sample MR analysis was conducted using summary statistics of genetic variants gained from 2 genome-wide association studies (GWAS) on circulating hcy and folate concentrations in individuals of European ancestry and from an independent GWAS study based on DIAMANTE meta-analysis. Results: In the observational study, after logistic regression with multiple adjustment, lower hcy and higher folate levels were identified to be associated with the risk of T2DM, with OR (95% CI) for hcy of 1.032 (1.003-1.060); while 0.909 (0.840-0.983) for folate. In the MR analysis, the OR for T2DM was 1.08 (95% CI: 0.95, 1.21; P = 0.249) for each SD unit increase in genetically predicted homocysteinemia and the OR for T2DM per SD increase in genetically predicted folate elevation was 0.80 (95% CI: 0.60, 1.00, P = 0.026).